Contradictions in schooling children among Mongolian pastoralists - Ahearn, A; Bumochir, D (Society for Applied Anthropology, 2016)
Mongolian pastoralist households with children face an annual decision at the start of the school year—how to take care of both herds and children separated by long distances and resource needs. This article draws on twelve months of ethnographic research on rural work practices among mobile pastoralists in Mongolia to illustrate how children's access to primary education spatially transforms the organization of herder livelihoods. By prioritizing herder reflections and theoretical insight into their own lives and experiences, we show that educating children within the conditions of Mongolia's emerging market macroeconomic system is entangled in struggles over housing, finance, and labor and we highlight the spatial nature of these contradictions in everyday rural social production. This evidence supports our argument that the terms of inclusion in Mongolia's current schooling system pose challenges for pastoralist livelihoods and encourages reflection on the need for imagining innovations in education provision.